A práxis de Antonio Delfim Netto no reordenamento político-econômico da ditadura bonapartista: ideólogo orgânico da autocracia burguesa brasileira - Rosa, Waldeir Moreno (2015)
This master's thesis analyzes the role of Antonio Delfim Netto in the various dimensions of political and economic power of bourgeois hegemony in the sixties and seventies. Initially, focuses on the historical period in which members of the Brazilian owning class associated with international capital, before compose the Bonapartist dictatorship established in 1964, have conspired against the constitutionally elected president, João Goulart, especially if extended into the Ipês complex (Institute of Economic and Social Research). Looks up at that first moment, on the class content of the article Problems of Brazilian economic development, especially prepared by the Dauphin to ipesiana magazine Convivium. In a second chapter, attentive to the participation of the economist at the National Association of Economic and Social Planning (ANPES), created by the conspirators to March 31, 1964, as a business front to influence the new business of the military dictatorship. Analyzes there, too, the book Planning for Economic Development of the then Secretary of the São Paulo State Finance. In the third chapter, after the so-called "coup within the coup", with the laying of the Bonapartist hardline and his dictatorial closing, we investigate the ideological reasons for the meteoric rise of the economist in the Ministry of Finance of the "years of lead" that is under Costa e Silva and Emilio Garrastazu Medici (1967-1974). At this point, enumerate up their participation in the "box" of Oban (Operation Bandeirante) and his vote in favor of the Institutional Act No. 5 in the National Security Council. Are analyzed, there, the official speeches the Minister considered the Czar Bonapartist political economy in his "years of lead", seeking to associate them with the practices of Delfim Netto attitudes and thus demonstrating the social function in the context of those years exercised by delfiniano ideological complex. That is, it is understood here delfiniana ideology in its social determination and particular historical context, deciphering the internal connection inherent to his autocratic bourgeois ideology, as well as explaining the effective function that fulfilled, in practice, the ideology of Brazilian economist. In view of Marx, with the advanced contributions by Chasin about Brazilian historical formation, has taken into account in the study of Delfim Netto, which is always "the man, the real, living man who does this, has it all and decides these combats; is not the story, you can be sure that, using man as a means to carry out - as if it were a person apart - their own ends; it is only the activity of the man who goes in search of himself. " Therefore, with all documentation found in newspapers, magazines, historiographical works, official speeches and events produced in the historical period under study, it remains more than proven the participation of Delfim Netto in class conspiracy, in the coup and the subsequent service who provided the political and economic reorganization of last Bonapartist dictatorship. Unfortunately, even today, however, its influence has continued, knowing the ideologue build for posterity one self-image of technocrat "neutral", supposedly the party or dissociated from all stratagems of state terrorism mounted in this country for the benefit of bourgeois autocracy atrophic capital. Its repeated denial before the crimes of the military dictatorship, registered in testimony to the Truth Commission of the City of 7 São Paulo, however, continues to separate and disassociate from manipulative way, made by Delfim Netto said about him by himself ideologue